DNA methylation is involved in pro-inflammatory cytokines expression in T-2 toxin-induced liver injury - Liu, Aimei; Sun, Yaqi; Wang, Xiaojing; Ihsan, Awais; Tao, Yanfei; Chen, Dongmei; Peng, Dapeng; Wu, Qinghua; Wang, Xu; Yuan, Zonghui (Food and chemical toxicology, 2019)
Currently, T-2 toxin has been reported to cause liver toxicity with the effects of oxidative stress and inflammation; however, the underlying mechanism of T-2 toxin-induced liver injury is not fully understood. Increasing lines of evidence show that DNA methylation affects the expression of inflammatory cytokine, and plays a crucial role in autoimmune diseases. Nevertheless, the potential role of DNA methylation in the hepatotoxicity of T-2 toxin has not been explored. In this study, female Wistar rats were given a single dose of T-2 toxin at 2 mg/kg b.w. and were sacrificed at 1, 3 and 7 days post-exposure. In vitro, a normal rat liver cell line (BRL) was exposed to different concentrations of T-2 toxin. Histopathological analysis was used to investigate damage to the liver, which was detected at the molecular level by RT-PCR, Western blot and immunohistochemical assays, methylation-specific PCR (MSP), bisulfite sequencing (BSP), and flow cytometry. The results showed that T-2 toxin significantly increased the levels of DNA methyltransferases (DNMT1, DNMT3A), which were mainly concentrated at the site of liver injury. The 5-methylcytosine (5-mC) level of genomic DNA was also raised in T-2 toxin-treated rat livers. The expression of inflammatory cytokines (IL-6, IL-1β, IL-11, IL-1α, and TNF-α) increased both in vivo and in vitro under T-2 toxin treatment. Notably, DNA demethylation directly increased the expression of cytokines IL-11, IL-6, IL-α, and TNF-α under T-2 toxin exposure. DNA methylation inhibitors combined with T-2 toxin directly or indirectly induced the production of inflammatory cytokines and aggravate cell apoptosis. Our study uncovered for the first time that DNA methylation is related to the expression of inflammatory cytokines in T-2 toxin-induced liver injury. These findings suggested that DNA methylation is a potential mechanism of T-2 toxin-induced hepatotoxicity.
Keywords: Inflammation Mediators; T-2 Toxin; T-2 toxin; Promoter Regions, Genetic; Rats; DNA methylation; promotorové oblasti (genetika); potkani Wistar; játra; mediátory zánětu; Animals; Liver; cytokiny; metylace DNA; Cytokines; Pro-inflammatory cytokine; zvířata; CpG ostrůvky; DNA Methylation; krysa rodu Rattus; Rats, Wistar; ženské pohlaví; Hepatotoxicity; Female; CpG Islands